Blood coagulation factor XII drives adaptive immunity during neuroinflammation via CD87-mediated modulation of dendritic cells - Kerstin Göbel (Nature Portfolio, 2016)
Factor XII initiates the intrinsic blood coagulation cascade and the kinin system. Here the authors show that Factor XII is elevated in the blood of multiple sclerosis patients, activates dendritic cells via CD87 and cAMP, and its blockade inhibits immunopathology in a mouse model of the disease.